Effectiveness of the Electronic System in Human Resource Development at Al-Awda Health and Community Association - Muhammad K. Hamdan; Ishaq Ibrahim; Mazen J. Al Shobaki (International Journal of Academic Accounting, Fina, 2024)
Non-Indexed Publication